Banking Crime in Money Laundering - Franky Ariyadi (International Conference On Law And Social Sciences, 2024)
Every year the Bank is required to improve its performance, especially the Bank's profit, then the Bank will expand or boost the distribution of funds (loans or credit). Thus, the source of the Bank's profit is still mostly from interest or proceeds from lending. Although the Bank wants to increase the portion of its loans, it is constrained by the amount of funds raised by the Bank. This research is a mixed methods study, with a convergent approach (combining quantitative and qualitative data to strengthen research findings and an exploratory approach (combining quantitative and qualitative data to gain a deeper understanding of complex research topics). Credit growth and liquidity fulfillment, money laundering, the nature of the Bank's business, the weakness of existing regulations, the role of government and stakeholder demands are things that can make the Bank involved in money laundering. Banks must be returned as institutions that prevent the entry of funds from criminal proceeds. It takes a comprehensive or holisitc solution to the problems that make banks involved in money laundering, where the business, the function of the Bank as an intermediary institution continues to run. A new business method is needed and can truly release the Bank from the dependence of liquidity that must be fulfilled.